Electronic Bond Structure of Carbon Nitride Thin Film Deposited by HiPIMS and dc Magnetron Plasma - Majumdar, Abhijit; Das, Sadhan Chandra; Stranak, Vitaslav; Hippler, Rainer (Journal of Coating Science and Technology, 2015)
We report the difference in electronic bond structure and surface chemical property of amorphous carbon nitride (a-CNx) film as a function of N/C which has been deposited by high power impulse magnetron sputtering (HiPIMS) and DC magnetron (dc-MS) plasma. The spectroscopic analyses suggest that the presence of oxide layer is the major cause for the surface charging in the core level peak. The core electron peaks (C1s, N1s and O1s) in x-ray photoelectron spectroscopy (XPS) show higher surface charging in HiPIMS compare to the film deposited by dc-MS plasma. The core peaks are moved gradually toward its virgin position as the etching duration is increased from 1 min to 80 mins. The films deposited by HiPIMS retain a higher N/C ratio following ion etching as compared to those deposited by DC magnetron sputtering suggesting denser films with a higher degree of cross-linking.